A 3D printed model for Singapore Changi Airport runway-taxiway for air traffic simulation and visualisation : part IV - Shahnas Farveen Mohamed Salim (Nanyang Technological University, 2020)
The purpose of this project was to project a 3D visualization of air traffic movement and hotspots at Changi Airport onto a 3D printed model of Changi Airport. The 3D model would be assembled from 3D printed pieces, utilizing a lego-concept. Moreover, the 3D printed Control Tower would have wireless cameras mounted on them to record and display the projection. The 3D visualization was designed via a projection mapping software called HeavyM. The 3D projection consisted of a static map of Changi Airport overlaid with a dynamic layer which consisted of aircraft movements. The individual components of the static map which included hotspots was designed on HeavyM. The animation for the dynamic layer required Google Map JavaScript adaptation to create aircraft movements. This animation was then overlaid onto the static map via HeavyM. The static map was displayed with vibrant colours while a translucent terrain view of the animation was overlaid to demonstrate contrast for enhanced visualization. The concept of projection mapping was utilized to ensure geometric alignment of the static and dynamic layers with the dimensions of the 3D model. This ensured the final display did not appear distorted. A short distance overhead projector was used to project the visualization vertically downwards with a slight tilt. It was observed that the size limitation of the equipment in the physical setup resulted in a compromise in the visibility of aircraft movements. This was overcome by managing the number of aircraft movements shown in the display. The final demonstration gave a better understanding of positions of hotspots and aircraft movements relative to a realistic 3D display of Changi Airport.